Nauka o motorike pered licom krizisa? - Daugs, R. (Teorija i Praktika fiziceskoj Kul'tury, 1997)
(Originally published under the title "Motorische Kontrolle ate Informationsverarbeitung: Vom Auf-und Niedergang eines Paradigmas". In: Blaser, P./Witte, Ê./Stucke, Ch. (eds.). Steuer-und Regelvorgänge der menschlichen Motorik. Academia. St. Augustin: 1994, pp. 13-37.) The aim of the following exposition is, on the basis of an overview of the general scientific advancement [1], followed by a review of the historical development of the psychology of information processing [2], to shed some light on the crisis of the approach by considering two of its basic assumptions, namely "time consumption" and "limited capacity" [3]. A crucial point will be the critical view of the human-computer analogy [4]. The recent "motor/action" controversy in motor control and learning research will be considered in some detail [5] and possible outcomes and perspectives for motor control and learning research (in sports) will be presented [6].